Generalized Joint Hypermobility: A Statistical Analysis Identifies Non-Axial Involvement in Most Cases - Mateus Marino Lamari; Neuseli Marino Lamari; Michael Peres de Medeiros; Matheus Gomes Giacomini; Adriana Barbosa Santos; Gerardo Maria de Araújo Filho; Eny Maria Goloni-Bertollo; Érika Cristina Pavarino (MDPI AG, 2024)
Context: Joint hypermobility (JH) represents the extreme of the normal range of motion or a condition for a group of genetically determined connective tissue disorders. Generalized joint hypermobility (GJH) is suspected when present in all four limbs and the axial skeleton, scored in prepubescent children and adolescents by a Beighton Score (BS) ≥ 6. Parameters are also used to identify GJH in hypermobile Ehlers-Danlos syndrome (hEDS) and hypermobility spectrum disorders (HSDs). The purpose of this study is to characterize children with JH based on the location of variables in the BS ≥ 6 and identify children with JH in the axial skeleton, upper limbs (ULs), and lower limbs (LLs) simultaneously. Methods: We analyzed 124 medical records of one- to nine-year-old children with JH by BS. Results: The characterization of GJH by combinations of the axial skeleton, ULs, and LLs simultaneously totaled 25.7%. BS = 6 and BS = 8 consisted of variables located in ULs and LLs. BS = 7 included the axial skeleton, ULs, and LLs. BS ≥ 6 represents the majority of the sample and predominantly girls. Conclusions: BS ≥ 6 represents the majority of the sample and predominantly girls. Most characterized children with GJH present BS = 6 and BS = 8 with variables located only in ULs and LLs, a condition that does not imply the feature is generalized. In children, BS = 7 and BS = 9 characterize GJH by including the axial skeleton, ULs, and LLs. These results draw attention to the implications for defining the diagnosis of hEDS and HSDs.